RADIATION-CONVECTION MODEL OF MOISTURE CIRCULATION IN THE EARTH`S TROPOSPHERE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
A radiation-convection calculation model of the troposphere and near-water surface atmosphere layer with a characteristic transverse size of 100-1000 km, contain moist air with water droplets is presented. Air turbulence due to free convection and advection is taken into account by B.I. Izvekov’s semi-empirical relation for the turbulent transfer coefficient , modified by L.T. Matveev. The influence of solar radiation is taken into account within the framework of a two-stream model with integral absorption parameters depending on the mass fraction of water vapor. Atmospheric air is represented as a dispersed mixture of moist air and water droplets. The processes of heat and mass exchange in the atmospheric column interacting with the surface ocean layer of wind mixing in the radiation-convective approximation are modeled. The influence of the parameters and convective wave properties of the model on non-stationary solutions that represent different heat and mass transfer modes near a smooth wave surface is considered.
Keywords: atmosphere, climate, ocean, radiation, system of equations, model.